Perlindungan Hukum Bagi Investor Terhadap Kejahatan Insider Trading Dalam Pasar Modal Indonesia - Leezza Salsa Salindeho; Gunardi Lie (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2025)
Insider trading is a crime that disrupts the stability of the capital market in Indonesia. This research focuses on evaluating legal protection for investors from insider trading practices under the Capital Market Law (UUPM) and exploring gaps in existing regulations. This research uses a normative-juridical analysis approach by reviewing literature on national legal norms and is also supported by case studies related to insider trading cases. The research findings indicate that although regulations regarding criminal, civil, and administrative sanctions exist, their implementation remains low. This is due to the lack of early detection mechanisms and compensation for victims, resulting in investors facing significant financial losses without adequate civil protection.